Phytoremediation of soil contaminated with plumbum and chromium using Lantana camara and Pilea cadierei with organic waste amendments / Alaribe Frank Ogenna - Alaribe Frank , Ogenna (2016)
Anthropogenic activities cause an estimated 10 billion tonnes of topsoil contamination from metals annually, this puts humans at risk because of metal trophic-level accumulation. This study was aimed at evaluating the efficiency of biowaste amendments, in phytoremediation of Pb and/or Cr contaminated soil, using 6% of empty fruit bunch (EFB) or spent mushroom compost (SMC) biowaste, with Pilea cadierei and Lantana camara plants on different Pb and/or Cr concentrations on (Mollisol) soil for 98 days, using a complete randomized experimental design. Based on the background and intervention guidelines from the Department of Environment (DOE) Malaysia on soil heavy metal standards. Results indicated Pb reductions between 52 to 88% and 45 to 82% in EFB and SMC amended soils under Lantana camara, and 44 to 83% and 42 to 79% for Pilea cadierei, respectively. Then 47 to 72% and 38 to 67% removal of Cr under Pilea cadierei, and also 53 to 75% and 46 to 72% for Lantana camara at similar order of biowaste above. Heavy metal resistant bacteria (HMRB) counts, pooled at 79.67 x 106 to 39.67 x 106 cfu/g, and 63.33 x 106 to 39.0 x 106 cfu/g were recorded at EFB and SMC metal-soils, respectively. Half-life’s (t1/2) of 7.24-2.26 days for (amended), 18.39-11.83 for (unamended), and 123.75-38.72 for (control) soils, were recorded. Bioaccumulation and translocation factors of Pilea cadierei and Lantana camara recorded < 1. Supposedly, a potential metallophytes. Freundlich isotherms, showed less Pb and Cr adsorption intensity (n) to soil between 2.44 to 2.51 when amended. Indicating opposite metal movement away from the bulk soil, via plant-root absorption, and ΔG also ranged -5.01 to -0.79 KJmol-1K-1 (exothermic), hence with intraparticle diffusion rate constant of 7.064 to 1.669 mg/kg-0.5. The pH of 5.02-6.03 was optimum for phytoremediation. In conclusion, Pilea cadierei and Lantana camara was sustainable in enhanced remediation of Pb and/or Cr contaminated soil, when amended with these biowastes.